Mapping Pluto's Republic: Cognitive and Epistemological Reflections on Philosophy of Pseudoscience: Reconsidering the Demarcation Problem - Ambasciano, Leonardo (Journal for the cognitive science of religion, 2015)
The presence of fringe and debatable methods and theories is widespread in the academia, excluding practically no discipline. Since theoretical reliability, epistemic warrant and empirical support are contentious issues, the demarcation between science and pseudoscience remains highly controversial, especially in the Humanities. However, a renewed interest in the demarcation problem holds much promise to tackle the underlying methodological and epistemological questions. This review essay briefly deals with the historiographical resilience of pseudoscience and the fascination which psi phenomena in the academic history of religion in the light of Massimo Pigliucci and Maarten Boudry's recently co-edited book, entitled Philosophy of Pseudoscience: Reconsidering the Demarcation Problem (Chicago, IL: The University of Chicago Press, 2013). A detailed review of Pigliucci and Boudry's volume is also provided.